Astaxanthin supplementation in Arabian racing horses mitigates oxidative stress and inflammation in peripheral blood mononuclear cells through enhanced mitophagy - Beata Giercuszkiewicz-Hecold; David Pajuelo; Zofia Steczkiewicz; Anna Cywinska; Krzysztof Marycz (Scientific Reports)
Abstract Astaxanthin, a strong antioxidant carotenoid, has shown promising features in mitigating inflammation and oxidative stress and so that has been considered as a supplement for high-performance animals. In this study, we aimed to evaluate the effects of astaxanthin on oxidative stress, inflammation, and mitochondrial health in peripheral blood mononuclear cells (PBMC) isolated from Arabian racehorses. Horse-derived peripheral blood mononuclear cells exposed to hydrogen peroxide (H₂O₂) presented increased reactive oxygen species (ROS) accumulation and overexpression of pro-inflammatory cytokines such as IL-1β, IL-6, IFN-γ, and TNF-α. The addition of astaxanthin to cell culture reduced H₂O₂-induced inflammatory response by decreasing the expression levels of all the tested pro-inflammatory cytokines. Moreover, astaxanthin displayed a potential antioxidant response by increasing the expression of genes related to antioxidative defense, such as NRF1, SOD2, and GPX. Interestingly, PBMCs isolated from the horses orally supplemented with astaxanthin increased the expression of the mitophagy-related genes PINK1 and PARKIN. Moreover, genes related to mitochondrial dynamics and energy production, such as PPARGC1B, NDUFA9, and MRPL24, as well as genes associated with mitochondrial function, structure and dynamics, such as PIGBOS, MRLP24, PUSL1 and TFAM were upregulated in PBMCs isolated from astaxanthin supplemented horses. Altogether, these findings indicate that astaxanthin may be a beneficial dietary supplement for equine health, supporting resilience against oxidative stress and inflammatory challenges, and improving the recovery and performance of racing horses.